2009
DOI: 10.1007/s00595-008-3835-2
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic leakage after low anterior resection for rectal cancer: Facts, obscurity, and fiction

Abstract: The subject of anastomotic leakage after low anterior resection (LAR) for rectal cancer remains controversial. Risk factors have been discussed in several studies but the findings are often inconclusive. This review evaluates these studies and separates the known risk factors into those that are well documented, those that are obsolete, and those that require further research. We searched the Medline and PubMed databases using the keywords: "leakage," "low anterior resection," "rectal cancer," "risk factors," … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 65 publications
8
65
2
5
Order By: Relevance
“…They also concluded that the distance of the anastomosis from the anal verge has a significant impact on anastomotic failure rates. They recommend the routine mobilisation of the splenic flexure and anastomosis of the descending colon, instead of the sigmoid, to the rectal stump (Taflampas et al, 2009). The use of a colonic J-pouch seems to decrease the leakage rates after low anterior resection.…”
Section: Anastomotic Leakagementioning
confidence: 99%
“…They also concluded that the distance of the anastomosis from the anal verge has a significant impact on anastomotic failure rates. They recommend the routine mobilisation of the splenic flexure and anastomosis of the descending colon, instead of the sigmoid, to the rectal stump (Taflampas et al, 2009). The use of a colonic J-pouch seems to decrease the leakage rates after low anterior resection.…”
Section: Anastomotic Leakagementioning
confidence: 99%
“…Although surgeons can expect that drain serves as an eye into the anastomosis [23], the anticipated warning function of prophylactic drain has been questioned. Urbach et al [7] showed in their meta-analysis that only 1 of 20 drains contained pus or enteric content at the time of diagnosis, resulting in a quite low sensitivity of 5% in detecting anastomotic leak.…”
Section: Early Indicator Of Anastomotic Leakmentioning
confidence: 99%
“…The route of drain can turn into a fecal fistula during the postoperative period [23], and this process is a fundamental principle of non-surgical, conservative treatment for anastomotic leak (Fig. 2).…”
Section: Therapeutic Use Of Drain In Management Of Anastomotic Leakmentioning
confidence: 99%
“…The incidence of clinically significant leakage after low anterior resection varies between 3% and 21%, but is thought to average 10%, or lower, when patients are operated by a high-volume surgeon. 7,8 Risk factors for anastomosis leakage like male sex, advanced age, overweight, low rectal cancer (10 cm from ano-rectal line), 3≥ Charlson index, high ligation of superior mesenteric artery, sepsis, neo-adjuvant chemotherapy, smoking, high American Society of Anesthesiologist (ASA) score, longer operative time (1.9), can be stratified by colon leakage score. 9,10 Intraoperative anastomosis check, good blood supply, tension free and meticulous operative technique are pre-requisites for better anastomosis healing.…”
Section: Introductionmentioning
confidence: 99%